Reinterpreting Mediation Success: Partial Agreements as Outcome-Based Justice in Divorce Cases at the Langsa Sharia Court - Nurul Husna; Muhazir Muhazir (Syarah: Jurnal Hukum Islam dan Ekonomi, 2026)
The success of divorce mediation in Indonesia has traditionally been measured by the achievement of full reconciliation between the disputing parties. Although Supreme Court Regulation No. 1 of 2016 recognizes the possibility of partial agreements (kesepakatan sebagian) during mediation, the administrative case-reporting system of the Religious Courts, namely the Case Tracking Information System (Sistem Informasi Penelusuran Perkara/SIPP), continues to treat full reconciliation as the primary indicator of mediation success. Consequently, partial agreements that substantively resolve the parties' post-divorce rights and obligations are not proportionately reflected in the evaluation of mediation performance. This research employs an empirical juridical method using a legal sociology approach based on Eugen Ehrlich’s theory of living law. The study explores the interaction between normative legal provisions and mediation practices that develop within judicial institutions. Data were collected through interviews, document analysis, and the examination of relevant legal regulations and academic literature. The analysis focuses on agreements concerning iddah maintenance, mut’ah, past maintenance (madhiyah), child custody (hadhanah), and child support. The findings indicate that partial agreements provide legal certainty regarding the rights and obligations of the parties and significantly reduce the potential for post-divorce conflict. Although such agreements do not result in reconciliation, they demonstrate the substantive function of mediation in resolving disputes and ensuring fairness. From the perspective of living law, these practices reflect a broader understanding of mediation success beyond the formal objective of preserving marriage. The findings indicate that, although partial agreements are recognized under Supreme Court Regulation No. 1 of 2016, they remain insufficiently reflected in administrative measures of mediation success. This study argues that mediation effectiveness should therefore be assessed not only by marital reconciliation but also by substantive legal outcomes that protect post-divorce rights and promote outcome-based justice.